Produção de material paradidático sobre infecções recorrentes entre adolescentes: um estudo de caso em uma instituição de ensino básico em Ibiúna, SP - Machado, Gabriela de Goes (Universidade Federal de São Carlos, 2025)
There are several infections that are recurrent among children and adolescents in Brazil, such as pediculosis; however, this parasitosis is often neglected and may directly compromise the individual’s physical and mental well-being. In light of this, the present study aimed to analyze the level of prior knowledge about this disease among students of a Private Basic Education Institution in the city of Ibiúna, São Paulo. Subsequently, paradidactic activities were developed for the target audience, such as interactive lectures and other support materials, with the purpose of verifying to what extent these methods could contribute to the process of building high-quality knowledge about this infection in the school context. The analysis considered data obtained from responses to two questionnaires: one applied at the beginning (before the intervention) and another at the end of the project (i.e., after the intervention), both containing closed-ended questions about symptoms, prophylaxis, treatment, and other relevant aspects of the infection. Although the questionnaires were not identical, but similar in terms of the required content, a marked improvement in the level of knowledge acquired about pediculosis after the paradidactic interventions used in this case study was observed. Based on the results obtained, it can be concluded that, although this infection is among the skills addressed in the São Paulo State Curriculum (Currículo Paulista), the approaches applied up to that point were not sufficient to promote meaningful learning of these contents. This demonstrates that the lecture delivered, together with the application of paradidactic materials, proved to be fundamental for the construction of students’ knowledge regarding aspects surrounding pediculosis, including, consequently, the recognition of their own bodies and the development of autonomy in identifying and preventing this disease. It is expected that this research will serve as a reference so that future practices in Science and Biology teaching, particularly regarding themes such as health and physical well-being, can be implemented through relatively simple paradidactic interventions that are, however, adequately planned according to students’ prior knowledge and that effectively assist in the construction of knowledge.
Production of supplementary educational material on recurrent infections among adolescents: a case study in a basic education institution in Ibiúna, SP
Keywords: Pediculose; Educação em Saúde; Pediculosis; Human Health; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; 4. Educação de Qualidade